2012
DOI: 10.1016/j.gie.2012.04.445
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and preliminary accuracy of high-resolution imaging of the liver and pancreas using FNA compatible microendoscopy (with video)

Abstract: Background-Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is one of the few techniques which can obtain cells and tissue from the liver and pancreas. However, the technique remains vulnerable to poor specimen quality and sampling error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…High‐resolution microendoscopy (HRME) is a low‐cost “optical biopsy” technology consisting of a 1‐mm‐diameter fiber optic bundle that allows for subcellular imaging at 1000× magnification at 4‐μm resolution. HRME has already been found to be effective in gastrointestinal pathology . In order for a complementary imaging tool to enhance the ability of WLE in classifying polyps, the modality must not only be inexpensive but also one that can be learned quickly and interpreted accurately.…”
Section: Introductionmentioning
confidence: 99%
“…High‐resolution microendoscopy (HRME) is a low‐cost “optical biopsy” technology consisting of a 1‐mm‐diameter fiber optic bundle that allows for subcellular imaging at 1000× magnification at 4‐μm resolution. HRME has already been found to be effective in gastrointestinal pathology . In order for a complementary imaging tool to enhance the ability of WLE in classifying polyps, the modality must not only be inexpensive but also one that can be learned quickly and interpreted accurately.…”
Section: Introductionmentioning
confidence: 99%
“…The simplicity, low cost, and real-time imaging performance of the HRME system have led to its use by several research groups in laboratory studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24] and in vivo clinical investigations [25][26][27][28]. However, the imaging properties of the HRME system have not been fully characterized; in particular, the axial imaging range and sensitivity to out-of-focus light have to the best of our knowledge, not been quantitatively studied.…”
Section: Introductionmentioning
confidence: 99%
“…3 In a feasibility, ex vivo (human tissue), in vivo (swine model) study of high-resolution microscopy imaging of the liver and pancreas (using topical proflavin solution and a probe through a 22-gauge needle), 9 endosonographers achieved median accuracy figures of 85% in the liver and 90% in the pancreas after a short-term training. 4 Optical coherent tomography (OCT) uses infrared light waves generating images by measuring the echo time delay and the intensity of back-scattered light. OCT technology can yield a lateral and axial spatial resolution of about 10 m. In a study involving 62 patients with superficial esophageal squamous cell carcinoma, OCT showed esophageal wall components that corresponded to the histological findings with an overall rate of 92.7% accuracy.…”
Section: Options For Management Of Anal Fissures Questionmentioning
confidence: 99%